Inter-Religious Communication in Islam: A Study on Answering and Greeting with a Sociological Approach - Hakim, Abdul (State Islamic Institute of Bone, Indonesia, 2024)
The purpose of this study is to explore inter-religious communication based on an understanding of the prophetic traditions through a sociological approach. Analyzing inter-religious communication based on Hadiths with a sociological approach is important. This study will propose two forms of Prophetic Interaction in addressing inter-religious communication, namely communication through associative interaction and dissociative interaction. The method used in this study is a descriptive qualitative method based on data and information sourced from the Prophet's traditions. Data were collected, then analyzed using a sociological approach. The findings of this study are that by examining the Prophet's traditions about inter-religious communication, especially in answering and giving greetings, it is not associated with the law of halal or haram. However, the prohibition and permissibility of answering and greeting non-Muslims are solely related to the social situations and conditions in which interactions are carried out with non-Muslims. Which basically can be divided into two forms or stages, namely associative which includes (cooperation, accommodation and assimilation) and dissociative forms or stages which include competition, contravention and conflict / dispute.